1988
DOI: 10.1038/333470a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of the major protein kinase C substrate of platelets

Abstract: In platelets, agonists that stimulate phosphoinositide turnover cause the rapid phosphorylation of a protein of apparent relative molecular mass (Mr) 40-47,000, called P47, by protein kinase C (PKC). Diverse identities have been ascribed to P47 including lipocortin, inositol 1,4,5-trisphosphate 5-phosphomonoesterase, pyruvate dehydrogenase alpha subunit and an actin regulatory protein. We have isolated human P47 clones by immunological screening of a lambda gt11 complementary DNA library from HL-60 cells, a hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(155 citation statements)
references
References 29 publications
6
149
0
Order By: Relevance
“…However, the number of potential interactions between signaling proteins may be increased further by another putative domain found within diverse proteins involved in intracellular signaling and/or in cytoskeletal function (Haslam et al, 1993;. Because this domain was identified initially as an internal N-and C-terminal sequence duplication in the major platelet substrate of protein kinase C, pleckstrin (Tyers et al, 1988), it has been named the pleckstrin homology, or PH, domain. In addition to pleckstrin, proteins that exhibit sequence similarity to this putative domain and that have been identified to date include the SH3 domain-binding protein 3BP-2, RasGAP and a RasGRF, the RAC family of serine/threonine protein kinases, the Drosophila and murine Sos proteins, Sec7p, the GTPase dynamin, the SH2 domain-containing protein Grb-7, oxysterol-binding protein, the yeast protein Bem3p, a trypanosomal protein kinase NrkA, the C. elegans Unc-104 kinesin-related product, the phospholipases PLCG and PLCy, and the P-spectrins (Haslam et al, 1993;.…”
Section: The Pleckstrin Homology (Ph) Domain: Another Putative Modulementioning
confidence: 99%
“…However, the number of potential interactions between signaling proteins may be increased further by another putative domain found within diverse proteins involved in intracellular signaling and/or in cytoskeletal function (Haslam et al, 1993;. Because this domain was identified initially as an internal N-and C-terminal sequence duplication in the major platelet substrate of protein kinase C, pleckstrin (Tyers et al, 1988), it has been named the pleckstrin homology, or PH, domain. In addition to pleckstrin, proteins that exhibit sequence similarity to this putative domain and that have been identified to date include the SH3 domain-binding protein 3BP-2, RasGAP and a RasGRF, the RAC family of serine/threonine protein kinases, the Drosophila and murine Sos proteins, Sec7p, the GTPase dynamin, the SH2 domain-containing protein Grb-7, oxysterol-binding protein, the yeast protein Bem3p, a trypanosomal protein kinase NrkA, the C. elegans Unc-104 kinesin-related product, the phospholipases PLCG and PLCy, and the P-spectrins (Haslam et al, 1993;.…”
Section: The Pleckstrin Homology (Ph) Domain: Another Putative Modulementioning
confidence: 99%
“…6; data not shown), both the labeled and nonlabeled cells were incubated for 5 h before treatment with various agents. Cells remained responsive to thrombin throughout the radiolabeling, as assessed by thrombin-induced shape change, aggregation, phosphorylation of myosin light chain-1 (a 20-kDa protein whose phosphorylation by a calmodulin-dependent kinase is stimulated by thrombin [11]), and phosphorylation of the 47-kDa protein kinase C substrate (identified as inositol 1,4,5-trisphosphate phosphomonoesterase [4], although doubts have been raised about this identification [24]). In some experiments (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Computer-assisted searches of protein sequence databases revealed that peptides A-E did not show significant homology to any known protein. These include two previously cloned protein kinase C substrates, namely P47 from platelets [21] and the neuronal protein GAP-43 [22].…”
Section: Resultsmentioning
confidence: 99%